'Could I Become Human by Engaging with Your Un(der)stated Life?' Struggles from a Psychoanalytical Perspective on Listening to the Mentally ill Poor Person and the Homeless Poor. (September 2015) - Vahali, Honey Oberoi
This article is concerned with the relationship that exists between mental health practitioners and historical survivors—the mentally ill poor patient and the homeless poor. The writing seeks to explore a possibility of authentic relatedness in which psychologists can listen to and engage with those who exist at socio-economic margins. The present effort is based in a belief that in dehumanising others and de-recognising the struggles of their existence, we dehumanise and split a part of our own humanity too. Our humanness is deeply connected to that of others and any aspiration towards growth is inseparable with how we relate with those whose dignity we continuously deny, by-pass or render insignificant. The disregard, apathy and indifference towards the mentally ill, poor and homeless in India (as elsewhere in the world) is so pronounced that at best we consider them as non-beings, at worst as the repositories of evil and all social ills. Rather than being able to question the oppressive social structure, the mental health context often perpetuates it. Some of the questions that this writing grapples with are—Is there a way for mental health professionals to break free and respond with empathy and genuine regard to the concerns that the poor mentally ill patient and the homeless poor bring to the fore through their specific modes of existence? Do we have access to a language of 'being and emotions' which is shared and which can make communication between 'us' and 'them', the 'self' and the 'other' a possibility? Have there been efforts in the past in which a regard for their emotions and existence has preoccupied us? And is there something that the intense, long-term engagement of psychoanalysis has to offer to such possibilities of relatedness. This article is an attempt to revisit and engage with some such concerns.